“I’ve Grown up with the Queen”: Responses to Media Coverage of Queen Elizabeth II’s Death - Kirsty Jane Anderson (Journalism and Media, 2025)
This study employs uses and gratifications theory and the news value of celebrity to explore comments from New Zealanders on the news coverage of the death of Queen Elizabeth II, New Zealand’s constitutional Head of State. Twenty-five participants kept a weekly diary of their news consumption and participated in focus groups to discuss their understanding of news. As the focus groups coincided with the media coverage of the Queen’s death, the participants discussed their responses to the news coverage of this event. These comments were classified by the sentiment expressed and analyzed in two age cohorts to explore the cognitive and affective responses of the participants. Overall, the participants over 26 years had more affective responses, and those under 26 years had more cognitive responses. With the older cohort, the participants experienced more media interactions with Queen Elizabeth II and had stronger grief responses and connections to her death, but it was hard to determine the full extent of any parasocial relationships. This paper concludes that uses and gratifications theory and news values can assist in understanding how audiences form connections to celebrities through the news media. In turn, these connections will impact how the news media cover celebrity deaths and the public mourning rituals of audiences.